Equivalent Modulus of Asphalt Concrete Layers - Amjad H. Albayati; Hasan Al-Mosawe; Aqeel T. Fadhil; Abbas A. Allawi (Civil Engineering Journal, 2018)
A flexible pavement structure usually comprises more than one asphalt layer, with varying thicknesses and properties, in order to carry the traffic smoothly and safely. It is easy to characterize each asphalt layer with different tests to give a full description of that layer; however, the performance of the whole; asphalt structure needs to be properly understood. Typically, pavement analysis is carried out using multi-layer linear elastic assumptions, via equations and computer programs such as KENPAVE, BISAR, etc. These types of analysis give the response parameters including stress, strain, and deflection at any point under the wheel load. This paper aims to estimate the equivalent Resilient Modulus (MR) of the asphalt concrete layers within a pavement structure by using their individual MR values. To achieve this aim, eight samples were cored from Iraqi Expressway no. 1; they had three layers of asphalt and were tested to obtain the MR of each core by using the uniaxial repeated loading test at 25 and 40 °C. The samples were then cut to separate each layer individually and tested for MR at the same testing temperatures; thus, a total of 60 resilient modulus tests were conducted. A new approach was introduced to estimate the equivalent MR as a function of the MR value for each layer. The results matched the values obtained by KENPAVE analysis.